Childhood vaccination timeliness following maternal migration to an informal urban settlement in Kenya. Issue 4 (28th January 2022) - Porth, Julia M.; Wagner, Abram L.; Treleaven, Emily; Fleischer, Nancy L.; Mutua, Martin K.; Braun, Thomas M.; Boulton, Matthew L.
Highlights: Extensive delays were observed; one-third of children received at least 1 dose late. Maternal migration does not appear to influence childhood vaccination timeliness. Characteristics of the migration experience similarly do not influence timeliness. Propensity score weighting addressed confounding common in migration research. Methods using left-censoring allowed inclusion of children without vaccination cards. Abstract: Introduction: Timely receipt of recommended vaccines is a proven strategy to reduce preventable under-five deaths. Kenya has experienced impressive declines in child mortality from 111 to 43 deaths per 1000 live births between 1980 and 2019. However, considerable inequities in timely vaccination remain, which unnecessarily increases risk for serious illness and death. Maternal migration is a potentially important driver of timeliness inequities, as the social and financial stressors of moving to a new community may require a woman to delay her child's immunizations. This analysis examined how maternal migration to informal urban settlements in Nairobi, Kenya influenced childhood vaccination timeliness. Methods: Data came from the Nairobi Urban Health and Demographic Surveillance System, 2002–2018. Migration exposures were migrant status (migrant, non-migrant), migrant origin (rural, urban), and migrant type (first-time, circular [previously resided in settlement]). Age at vaccine receipt (vaccination timeliness) was calculated for all basic vaccinations. Accelerated failure time models were used to investigate relationships between migration exposures and vaccination timeliness. Confounding was addressed using propensity score weighting. Results: Over one-third of the children of both migrants and non-migrants received at least one dose late or not at all. Unweighted models showed the children of migrants had shorter time to OPV1 and DPT1 vaccine receipt compared to the children of non-migrants. After accounting for confounding only differences in timeliness for DPT1 remained, with the children of migrants receiving DPT1 significantly earlier than the children of non-migrants. Timeliness was comparable among migrants with rural and urban origins and among first-time and circular migrants. Conclusion: Although a substantial proportion of children in Nairobi's informal urban settlements do not receive timely vaccination, this analysis found limited evidence that maternal migration and migration characteristics were associated with delays for most doses. Future research should seek to elucidate potential drivers of low vaccination timeliness in Kenya.